Pengaruh Literasi Digital Terhadap Perilaku Pencarian Informasi Mahasiswa Fakultas Teknologi Informasi - Bernadedta Bernadedta; Anton Hermawan; Tintien Koerniawati (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2023)
This research was aimed to examine the effect of digital literacy on the information seeking behavior of Information Technology faculty students class of 2019, Satya Wacana Christian University. Data collection was carried out by distributing 100 questionnaires directly to 2019 batch of information technology faculty students as respondents. The research method used is quantitative. The method used is simple linear regression analysis, by testing the statistical hypothesis t-test. The results of the study show that digital literacy influences the information seeking behavior of students of the Faculty of Information Technology class of 2019 at Satya Wacana Christian University. The magnitude of the influence of digital literacy on information seeking behavior is 65.9 percent of information seeking behavior (Y) is influenced by digital literacy while the remaining 34.1% is influenced by other factors such as libraries, reading gardens, and others.